The influence of motivation, communication, leadership style on employee performance at the office of supervision and customs service & excise type c bontang - Junaid Kamaruddin, Muhammad; Sariwulan, Tuty; Suhud, Usep (Journal of Business and Behavioural Entrepreneurship, 2022)
This research investigates and analyzes the influence of variables of Motivation, communication, leadership style on employee performance on employee performance variables at the Office of Supervision and Customs & Excise Service Type C Bontang Customs. These variables in this study are referred to simultaneously, for example, endogenous variables: Motivation (X1), Communication (X2), Leadership Style (X3), (While endogenous or dependent variables (dependend variables) are Performance (Y). using primary data, namely data obtained from respondents directly from interview results or the results of filling out questionnaires collected through field surveys. And secondary data is data that is taken indirectly, namely data that has been processed by agencies, in the form of reference books, reports. The data analysis used in this study is qualitative analysis and quantitative analysis. The population used is employees at the Bontang Customs Supervision and Service Office type C Customs Which amounts to 113 people. By using the jebuh sample method, that is, all populations become samples. using spss for Windows programs ver 22.0 and AMOS ver 22.0. Motivation has a significant effect on employee performance, this shows that the higher the motivation, the more it will improve employee performance. Communication has a significant effect on performance, this shows that the better the communication will make the higher the employee’s performance. Leadership Style does not have a significant effect on employee performance, this shows that leadership style does not have a direct effect on employee performance.